Episiotomía y disfunciones del piso pélvico femenino - Guzmán R., Rodrigo; Aleuanlli A., Maria Cristina; Castro L., Ariel; Naser N. , Michel; Wenzel D., Carlos; Castro C., Daniela; Manríquez G., Valentín (Revista Hospital Clínico Universidad de Chile, 2015)
Pelvic floor dysfunctions are highly prevalent in our population significantly affecting the quality of life of women. Pregnancy and childbirth are well recognized risk factors. It has recently become clear that pelvic floor trauma encompass more than perineal trauma or “what one could see in the delivery room.” The levator ani muscle may be affected at birth with the loss of the integral structure of the pelvic floor support, secondarily triggering the descent of the pelvic organs. The overdistension of the urogenital hiatus and anal sphincter injuries can also be consequences of a vaginal birth. An episiotomy is an intervention that seeks to facilitate the expulsion of the fetus expanding the perineum preventing tissue distension and perineal tear. However, this claim raised by its developer has no scientific basis. Today the restrictive practice of this procedure is recommended, given the potential complications that may arise when it is systematically performe. Despite this recommendation, there are no conclusive studies that explore the role that episiotomy has in obstetric pelvic floor trauma.